Membuat keputusan klinikal dalam skala kejururawatan - Mohamed Ludin, Salizar (2021)
This questionnaire was translated into Bahasa Malaysia and used as a tool in a study on Critical Thinking and Decision Making Among Nurses in Critical Care Areas